ANALYSIS ABOUT POLITENESS IN “BARBIE AS THE PRINCESS AND THE PAUPER MOVIE” - Viren Aulia Angginie; Tika Santika; Ula Nisa El fauziah (IKIP Siliwangi, 2019)
Abstract Pragmatics aims to give an overview of the politeness principles, to describe and to explain the types and functions of Face Threatening Act (FTA) and Face Saving Act (FSA) use in relation with politeness in the conversation by the characters in Barbie as The Princess and The Pauper movie. The oral utterances are analyzed and interpreted descriptively based on Brown and Levinson’s Face Threatening Acts theory and George Yule’s theory. This research employs descriptive qualitative method and supported by percentage calculation. To collect the data, the researchers use some steps; collecting the conversation by watching it and listening the conversations carefully, use fields note. Finally, the result of the research shows there are two kinds of FTA and FSA that used by the characters, negative FTA and positive FTA and FSA. In Barbie as the Princess and the Pauper movie, the data shows the using of FTA talked by Princess Anneliese is 3,6% and by Preminger is 5% . It shows that Preminger more dominants in using FTA than Princess Anneliese. About FSA, Princess Anneliese is 3,6% and Preminger is 6,8%. Preminger likes to talk in FSA ways and Princess Anneliese as same as in using FTA and FSA.Keywords: Politeness, Face Threatening Act, Face Saving Act, Barbie Movie.